2010
DOI: 10.1155/2010/742307
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships of Tetraploid AB-Genome Avena Species Evaluated by Means of Cytogenetic (C-Banding and FISH) and RAPD Analyses

Abstract: Tetraploid oat species Avena abyssinica, A. vaviloviana, A. barbata, and A. agadiriana were studied using C-banding technique, in situ hybridization with the 45S and 5S rDNA probes, and RAPD analysis in comparison with the diploid species carrying different types of the A-genome (A. wiestii, As; A. longiglumis, Al; A. canariensis, Ac; A. damascena, Ad, A. prostrata, Ap). The investigation confirmed that all four tetraploids belong to the same AB-genome group; however A. agadiriana occupies distinct position am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
34
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 47 publications
12
34
2
1
Order By: Relevance
“…Four recognized species have been proposed to have an AB genome composition. Of these, A. barbata, A. abyssinica and A. vaviloviana are grouped into a biological species known as the barbata group, while A. agadiriana is distinct [25, 42]. Our results confirmed the reported structural differences between these two groups (Fig 3).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Four recognized species have been proposed to have an AB genome composition. Of these, A. barbata, A. abyssinica and A. vaviloviana are grouped into a biological species known as the barbata group, while A. agadiriana is distinct [25, 42]. Our results confirmed the reported structural differences between these two groups (Fig 3).…”
Section: Discussionsupporting
confidence: 87%
“…Recently, another GBS study [19] showed that the AB genome tetraploid species fell into a tight cluster with A s genome diploids, also supporting the hypothesis that the B genome arose through minor divergence following autoploidization. However, other evidence from C-banding [24], FISH [17], RAPD markers [25], and DNA sequence alignment [14] has indicated a clear distinction between A and B genomes, suggesting an allotetraploid origin of the AB genome tetraploid species. The most probable A genome progenitor of the AB genome tetraploids is assumed to be an A s genome diploid species, while the B genome of these species remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Two long‐time proposed evolutionary models can accommodate our results and the accumulated evidence to explain how the constituent subgenomes may have arisen: (i) an autotetraploid origin of the two more similar subgenomes As_2 and As_3 (A/D), and subsequent hybridization with a C genome (Badaeva et al ., ; Ladizinsky, ); and (ii) an allotetraploid formation with two close A genome species and later subgenome divergence (Fu and Williams, ; Ladizinsky, , ). Nevertheless, to date, none of them have been unequivocally substantiated as participating in the formation of the hexaploid species.…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization (Jellen et al 1994;Yang et al 1999;Shelukhina et al 2008) also provides evidence for the close relationship between these two species. There is ample evidence that the AABB genome tetraploid species A. barbata, A. abyssinica and A. vaviloviana are autotetraploid derived from the A s A s genome diploid species (Ladizinsky & Johnson 1972;Leggett & Markhand 1995;Katsiotis et al 1997;Loskutov 2008;Badaeva et al 2010). In the present study, these three AABB tetraploid species also showed a close relationship with the A s A s genome diploid species.…”
Section: Relationships Among Avena Speciesmentioning
confidence: 99%